The Effect of Doubling the Amount of Recess on Elementary Student Disciplinary Referrals and Achievement Over Time. Issue 4 (2nd October 2019) - Erwin, Heather; Fedewa, Alicia; Wilson, Jason; Ahn, Soyeon
ABSTRACT: Research demonstrates children's attention, working memory, and behavior improve following a recess or activity break. Longer periods of inactivity are associated with higher levels of inattention; children who are less active have higher rates of disciplinary infractions. Thus, providing physical activity breaks may positively impact student achievement and behavior. The purpose of this study was to determine the effect of doubling recess time on elementary students' academic achievement and disciplinary referrals over two school years. Participants were 728 K to 6th-grade students from one school in the southeastern United States who transitioned from one 15-minute recess break to two 15-minute recess breaks per school day the following year. Discipline referrals were recorded and coded by type. Academic achievement reflected students' math and reading performance on the Measure of Academic Progress, the Reading Inventory, and the Math Inventory. Results show the number of discipline referrals increased with the additional daily recess, and math test scores improved. Given the differential effects on student disciplinary referral and academic achievement outcomes, implications are discussed for school personnel in light of these findings.